Uso de gráficos de controle no monitoramento de infecções relacionadas à assistência à saúde na unidade de terapia intensiva - Dantas, Thayana Rose de Araújo (2018)
Infections have a significant impact on morbidity and mortality, lead to high expenditure of resources, and are thus recognized as a serious public health problem. Health control charts can be applied in the surveillance setting and control of infections. The aim of the present study is to use control charts in the monitoring of Healthcare-Associated Infections (HAIs) as a support for decision-making processes in the general Intensive Care Unit (ICU). This is an observational, descriptive, ecological epidemiological study with a quantitative approach. Secondary source data from consultations to monthly epidemiological bulletins issued by the Hospital Infection Control Commission (Portuguese acronym: CCIH) of a university hospital were used, and they included statistics from January 2014 to September 2017. The following variables were chosen for monitoring the occurrence of HAIs in ICUs by using control charts: HAIs’ patients, HAIs, patients/day, HAIs rate, UTI (urinary tract infection), UC (urinary catheter)/day, ID (incidence density)-UTI, ID, PNM (pneumonia), MV (mechanical ventilation)-day, ID-PNM, BI (bloodstream infection), CVC (central venous catheter)-day and ID-BI. The control charts were developed and evaluated, and then variables were monitored. Taking into account the type of variable monitored, the following charts were selected for attributes: u, p and beta charts. The u-chart monitored the general infection using the HAIs rate variable. P and beta charts monitored the proportion of patients with infection by using the HAIs patient and patient/day variables, and the specific infections (UTI, PNM and BI). Finally, the use of control charts can be useful for monitoring HAIs in the ICU. The charts applied in this study demonstrated good performance for monitoring the indicators over time. This control method allowed the efficient surveillance of infections, since it enabled the visualization of trends of increase and reduction of infections in a timely manner. This is an important resource of decision making for hospital management. It is possible to glimpse its use in the most varied services with application to different health indicators.